(untitled) (Herald of the National Children’s Medical Center, 2022)
Celiac disease affects 0.5-1% of the world’s population, there is a steady increase in gluten intolerance. Celiac disease is a multifactorial pathology. The aim of the study was to estimate the effect of the nutraceuticals L-glutamine and colostrum on the dynamics of clinical manifestations and the state of small intestine permeability and absorption in children with celiac disease. We examined 76 children with celiac disease aged 11 months to 14 years, who were treated at the Republican Specialized Scienti^c and Practical Medical Center for Pediatrics (RSSPMC of Pediatrics) from November 2015 to September 2019. To assess the effectiveness of drugs in the complex treatment of children with celiac disease, 2 groups of patients were compared: the ^rst group, which included 25 patients who received basic therapy and the second group - 22 children on modi^ed treatment (basic therapy + “L-glutamine and colostrum).Based on the data obtained, the positive effect of glutamine and colostrum on the main clinical manifestations of the disease, complications and contributes to the improvement of cavity, membrane digestion, intestinal absorption and permeability has been proven.